PERAN MEDIA SOSIAL SEBAGAI SARANA DALAM PUBLIKASI TUGAS DAN FUNGSI KEPOLISIAN DI POLDA BALI - I Gede Febriana Wisnu Saputra; I Wayan Gde Wiryawan (Jurnal Hukum Mahasiswa, 2021)
The existence of the police is very closely related to the community. At present, the good reputation of the police in the eyes of the public is often tarnished by the actions of the individuals themselves who often make mistakes against the public in the field, resulting in the emergence of criticism and the reputation and credibility of the police. In line with these problems, in order to realize good governance, the police are currently trying to change the paradigm in the public relations sector as an alternative solution for the police to be more active in disseminating information related to performance through various media including the media. social services so that the public still trusts the police and can better understand the policies taken by the police in carrying out their duties. This study aims to analyze the role of social media in the publication of the duties and functions of the police and what factors influence the use of social media by the police at the Bali Police. This research contains empirical legal research, using descriptive research and using qualitative data analysis. From the research conducted, it is known that the role of social media in the publication of the duties and functions of the police at the Bali Police, including as a technical communication, communication facilitator and problem solving. Furthermore, there are two factors that influence the use of social media as a means of publication by the police, namely internal factors and external factors. The internal factors that influence are the development of technology and information, while the external factors that influence are caused by the fact that there are still many people who do not believe in the police